Melatonin and cardiovascular disease: from mechanisms of action to potential clinical use (literature review) - O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Cardiovascular disease remains the most relevant public health problem. Most cardiovascular diseases are associated with an atherosclerosis, the development of which is associated with inflammation and endothelial dysfunction. Melatonin is a neurohormone that is synthesized mainly in the pineal gland and plays a central role in the regulation of sleep and some other body cyclic processes. For a long time, melatonin was perceived as a substance that is effective in the treatment of circadian cycle impairments. At the same time, a large number of studies have accumulated recently that demonstrate a wider range of its biological effects, including anti-inflammatory, antioxidant, antihypertensive and, possibly, hypolipidemic. The review includes current data from experimental and clinical studies demonstrating the cardioprotective effects of melatonin in atherosclerosis, myocardial ischemia, and heart failure.